Assessing the cultural competence of oral health research conducted with migrant children. Issue 1 (22nd July 2013) - Riggs, Elisha; Gussy, Mark; Gibbs, Lisa; van, Caroline; Waters, Elizabeth; Priest, Naomi; Watt, Richard; Renzaho, Andre M. N.; Kilpatrick, Nicky
Abstract Objectives Traditional assessment of research quality addresses aspects of scientific rigor, however, ensuring barriers to participation by people of different cultural backgrounds are addressed requires cultural competence. The aim of this research was to assess the cultural competence of oral health research conducted with migrant children. Methods A protocol was developed with explicit inclusion and exclusion criteria. Electronic databases were searched from 1995 to 2009. Each study was assessed for cultural competence using the assessment criteria and a template developed as a proof‐of‐concept approach. Results Of the 2059 articles identified, 58 met inclusion criteria (n = 48 studies). There were four (8.3%) cohort studies, five (10.4%) intervention studies, 37 (77.1%) quantitative cross‐sectional studies, and two (4.2%) were qualitative studies. Overall, migrant children had worse oral health outcomes in all studies compared with their host‐country counterparts. All studies rated poorly in the cultural competence assessment. Conclusions Appropriate inclusion of all potentially vulnerable groups in research will result in better estimates and understandings of oral health, and more reliable recommendations for prevention and management.